Cross-Border Labor Migration in Europe: A View from the Emerging Civil Society in Ukraine - Dubnyak, Maksymilian; Koshmanova, Olena (Journal of Education Culture and Society, 2020)
Using acase study approach, the paper analyzes available research on the topic of identifying and the effects that cross border wage labor migration makes on the Ukrainian family and on the development of the emerging civil society in Ukraine. The goal of the article is two-fold: to enrich the pool of knowledge on Ukrainian female migrants to Europe, and to engage with recent literature on the role that transnational migration plays in relation to the family and the sending country as part of transnational civil society